Tribological and Corrosion Behavior of AISI 1045 Coated with AISI 316 Film Produced By Triode Magnetron Sputtering - Silviane C. F. Gorski; Bruno Nunes; Abel A. C. Recco; Cesar E. da Costa; Marcus V. F. Schroeder; Julio C. Giubilei Milan (Materials Research, 2024)
Recent studies have demonstrated mechanical, tribological and corrosion improvements properties on raw materials coated with stainless steel films produced by magnetron sputtering. However, few studies have reported the tribological behavior of thin austenitic stainless-steel films applied to the surface of carbon steels. The present study investigated the tribological behavior of AISI 1045 carbon steel coated with AISI 316 stainless steel film. Pin-on-disc dry sliding wear test was performed. The wear tracks were analyzed using a scanning electron and confocal microscopes. The corrosion resistance of coated and uncoated AISI 1045 were also assessed through an electrochemical test. Samples which presented a mixture of α-Ferrite and γ-iron, with predominant austenite parts, demonstrated lower friction coefficient, lower wear rates, and better corrosion resistance compared to substrate material. The results were also influenced by the variables used in the deposition process, as observed, heating the substrate and submitting to a higher powder density could improve the results. The results found corroborate to the academic and industrial research which looks for coating alternatives to AISI 1045 tools.